CLINICAL CHARACTERISTICS OF RESPIRATORY INVOLVEMENT IN CHILDREN WITH CYSTIC FIBROSIS IN THE CHUVASH REPUBLIC - N. B. Semenova ("Paediatrician" Publishers LLC, 2012)
The complaints on relapsing abdominal pain in children are not uncommon in paediatric practice. It is known, that approximately 50%of pains are caused by psychogenic factors, so such patients demand specialized psychological and psychotherapeutic medical care. The aim of this study was to establish the association between relapsing abdominal pain in children with emotional disturbances and social environment in development of this disease. The study included 2 groups of patients - with and without relapsing abdominal pain, 100 children in each group. During the study the authors used the clinical method of psychiatric interviewing, the modified method of E. G. Eidemiller's and V. V. Justitskis's «Standard family condition», A. J. Vargi's and V. V. Stolin's questionnaire of the parental care. It wasshown, that 88% of children with relapsing abdominal pain had complaints on mental health: fatigability (61%), headaches (62%), sleep disturbances (33%), anxiety (46%), disturbances of mood (19%). The most significant psychogenies are stress factors related to school. Relapsing abdominal pain can also be caused by parental deprivation. Therefore, 65% of children with abdominal pain need specialized psychological or psychotherapeutic medical care.